Answer:
-7pi √3
Step-by-step explanation:
Treating pi as a variable, the simplified value can be written as;
-7pi √3
This can be obtained from using the following simple methodology;
pi(√3 -8 √3)
= pi (-7 √3)
The answer is the third one aka C.
There must not be two points on the same y-axis because that doesn't make a function but a relation instead.
C. doesn't have 2 points on same y-axis and therefore the third picture is the relation that's a function.
Answer:
because 1+1 adds up to 2
Step-by-step explanation:
Hi there! :)
Answer:
![\huge\boxed{n = -2}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7Bn%20%3D%20-2%7D)
5n + 6 = -3n - 10
Solve for n:
Add 3n to both sides:
5n + 3n + 6 = -3n + 3n - 10
8n + 6 = -10
Subtract 6 from both sides:
8n + 6 - 6 = -10 - 6
8n = -16
Divide both sides by 8:
8n/8 = -16/8
n = -2.
Answer:
The first blank: not equal
The 2nd blank: not right triangle (it's acute triangle)
The 3rd blank: equal
The 4th blank: it's right triangle
Step-by-step explanation:
4^2 = 3^2 + 3^2
<=> 16 = 9 + 9
<=> 16 = 18 ( nonsense)
so triangle LKJ is not right triangle
5^2 = 4^2 + 3^2
<=> 25 = 16 + 9
<=> 25 = 25 ( make sense)
so triangle ABC is right triangle
Done!! :))